Metabolic profiling on the effect of 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) in MCF-7 cells. (February 2018) - Wei, Juntong; Xiang, Li; Yuan, Zigao; Li, Shangfu; Yang, Chunxue; Liu, Hongxia; Jiang, Yuyang; Cai, Zongwei
Abstract: Polybrominated diphenyl ethers (PBDEs) are commonly used to prevent the development of fire in various factory products. Due to the adverse effects on human health and the bio-accumulation capacity, PBDEs are considered as one kind of persistent organic pollutants (POPs). BDE-47 is one of the most frequently detected PBDEs congeners in human samples. Although numerous studies have shown the close connection between BDE-47 and human health, few reports were related to breast carcinoma. In the present study, the toxicity mechanism of BDE-47 was investigated by using MCF-7 breast cancer cells. Metabolomics analysis was conducted by using ultra-high performance liquid chromatography coupled with mass spectrometry (UHPLC-MS). Results showed that the toxicity to MCF-7 cells gradually increased when the concentration of BDE-47 exceeded 1 μM in the medium with 1% fetal bovine serum (FBS). It was found that pyrimidine metabolism, purine metabolism and pentose phosphate pathway (PPP) were the most influenced metabolic pathways, and the metabolites in the three metabolic pathways were significantly downregulated. Moreover, the increase of reactive oxygen species (ROS) was detected by using the 2′, 7′-dichlorodihydrofluorescein diacetate (DCFH-DA) staining method. The obtained results suggested that the BDE-47 induced oxidative stress by downregulating the NADPH generation in PPP. The pyrimidine metabolism and purine metabolism might be downregulated by the downregulation of mRNA transcripts. Therefore, BDE-47 could induce oxidative stress by inhibiting PPP and disorder the metabolism of the entire cell subsequently. This research provided evidence for investigating mechanism of the adverse effect of BDE-47 on human health. Highlights: The toxicity of BDE-47 to MCF-7 cells was studied by using metabolomics strategy. BDE-47 showed dose-dependent toxicity to MCF-7 cells. BDE-47 upregulated the reactive oxygen species by inhibiting the generation of NADPH in pentose phosphate pathway. BDE-47 downregulated purine and pyrimidine metabolism.